Aldous Huxley and Alternative Spirituality - Poller, Jake, (Aries Book Series ;, 2019)
Aldous Huxley and Alternative Spirituality offers an incisive analysis of the full range of Huxley's spiritual interests, spanning both mysticism (neo-Vedanta, Taoism, Mahayana and Zen Buddhism) and Western esotericism (mesmerism, spiritualism, the paranormal). Jake Poller examines how Huxley's shifting spiritual convictions influenced his fiction, such as his depiction of the body and sex, and reveals how Huxley's use of psychedelic substances affected his spiritual convictions, resulting in a Tantric turn in his work. Poller demonstrates how Huxley's vision of a new alternative spirituality in Island , in which the Palanese select their beliefs from different religious traditions, anticipates the New Age spiritual supermarket and traces the profound influence of Huxley's ideas on the spiritual seekers of the twentieth century and beyond.